Bone. 2 : the great cow race - Smith, Jeff, 1960 February 27- (Bone, 2005)
Now that they are reunited, Fone Bone, Phoney Bone, and Smiley Bone plan to return home, but Phoney Bone risks everything on a get-rich-quick scheme and it all goes wrong. Plus, a war is brewing and Fone Bone helps his new friends to defend their idyllic valley from a formidable enemy.